Does Gender and Academic Year Affect The Performance of Entrepreneurship Education? - Christina, Christina; Christian, Timotius Febry; Utami, Christina Whidya; Kristanti, Lili (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2022)
Entrepreneurship education has received special attention from Indonesia government in the last 10 years. It is one of the government programs to increase the number of entrepreneurs to support Indonesia’s vision to become a developed country in 2045. Research on gender issues and women entrepreneurship have attracted attention, thus increased tremendously. Yet, there are still few scholars whose research is about the relationship between gender and entrepreneurship academic performance, especially in Indonesia. This study aims to compare entrepreneurship subject final score, using gender and academic year as the independent variables. The data used in this study is secondary data taken from the academic system. There are 3336 data used in this research. There are four levels of the academic year and there are 834 data in each academic year, consist of 374 males and 460 females. The comparative test is analyzed using a two-way ANOVA. The result of this study shows that there is a significant difference between the male and female final scores on entrepreneurship subjects from the second semester until the fifth semester. Females tend to have higher scores compared to males. The result of this study also shows that there is a significant difference in the final score between each academic year. The result of the two-way ANOVA shows that there is no interaction between academic year and gender. Based on the finding, it is recommended to do further research to find the reason behind the good achievement by female.